2009
DOI: 10.1039/b909556j
|View full text |Cite
|
Sign up to set email alerts
|

N-Hexyl-4-aminobutyl glycosides for investigating structures and biological functions of carbohydrates

Abstract: The potential applications of N-hexyl-4-aminobutyl glycosides in the mass spectrometric investigation of glycan structure and in the investigation of glycan functions were studied. Under collision-induced dissociation (CID) conditions, sodiated glycosides carrying N-hexyl-4-aminobutyl groups effectively produced a hemiacetal species (C-ions), which is important in mass-spectrometry-based structural investigation. The usefulness of N-hexyl-4-aminobutyl glycosides in biological analysis was also confirmed by obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Further investigation on glycosphingolipids obtained from cultured cells is in progress to reveal the regulatory mechanism of glycan synthesis in our laboratory. 23,24 We envision that the system will become an important platform in glycomics research.…”
Section: Discussionmentioning
confidence: 99%
“…Further investigation on glycosphingolipids obtained from cultured cells is in progress to reveal the regulatory mechanism of glycan synthesis in our laboratory. 23,24 We envision that the system will become an important platform in glycomics research.…”
Section: Discussionmentioning
confidence: 99%
“…When this conjugate was fed to a PC-12D cell culture, it was possible to visualize specific Golgi vesicles through fluorescence confocal imaging. Fluorescently labelled glycans were also shown to be useful in tracking the internalization and cell activation of inositol phosphate glycans [51], to profile cytoplasmic peptide:Nglycanase [52] or other glycosidases [53], and cell targeting and uptake of glycans [54][55][56].…”
Section: Fluorescently Labelled Glycans For Intracellular Applicationsmentioning
confidence: 98%
“…Taking advantage of synthetic chemistry, it was reported that the carbohydrate C-ions could be generated stereo-specifically in gas phase, from the corresponding 4-aminobutylglycosides [67,68]. This particular glycoside with an amino group could also be utilized in preparing the required conjugates for biological investigations [69].…”
Section: Suitable Ion Species For the Structural Analysismentioning
confidence: 99%